A laser cladding composite coating and preparation method thereof

Through the three-beam laser cladding technology, combined with the mixture of nickel-based alloy and flux-core welding wire, the problem of stress concentration in diamond composite coating during laser cladding is solved, and the coating is achieved with high wear resistance and stability.

CN117604519BActive Publication Date: 2025-04-08ZHENGZHOU RES INST OF MECHANICAL ENG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311614200.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-29
Publication Date
2025-04-08
Estimated Expiration
2043-11-29

AI Technical Summary

Technical Problem

Diamond composite coating is prone to stress concentration during laser cladding, resulting in cracks and poor performance, limiting its application.

Method used

The cladding is carried out by three-beam laser. The first laser is preheated, and the second laser is sent to the second nickel-based alloy simultaneously for cladding. The third laser heats the flux-core welding wire to melt and mix it with the nickel-based alloy to form a wear-resistant layer distributed in diamond to avoid stress concentration.

Benefits of technology

It improves the wear resistance and use stability of the coating, extends the service life of the workpiece, and significantly improves the wear resistance and reliability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117604519B_ABST
    Figure CN117604519B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of metal coatings, and specifically relates to a laser cladding composite coating and a preparation method thereof. In the preparation method provided by the present invention, when preparing the wear-resistant layer, the first laser beam is used for preheating, the second laser beam is synchronously fed into the second nickel-based alloy for cladding, and the third laser beam is used to heat the flux-cored welding wire, so that the flux-cored welding wire is melted and mixed with the second nickel-based alloy, thereby concentrating the diamonds on the upper surface of the wear-resistant layer to increase the wear resistance of the coating. The coating of the present invention adopts a three-layer gradient transition cladding layer structure of a transition layer, a slow-release layer and a wear-resistant layer, which can effectively alleviate the stress concentration caused by the large difference in the physical and chemical properties between the base material and the diamond, avoid the formation of cracks in the coating, improve the wear resistance and performance of the coating, and ensure the safe and reliable service of the parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal coatings, and in particular relates to a laser cladding composite coating and a preparation method thereof. Background Art

[0002] Applying wear-resistant functional coatings on the surface of parts can effectively improve the surface wear resistance of parts and extend their service life. As engineering machinery and equipment develop towards high efficiency, high quality and long life, higher requirements are also put forward for the wear-resistant coatings on the surface of key parts.

[0003] Diamond has the characteristics of high hardness, good wear resistance and high thermal conductivity. It is mixed with Ni-based, Co-based, Fe-based and other alloy powders to prepare a composite coating structure with wear-resistant particles embedded in a tough matrix. It can effectively improve the wear resistance of the coating and extend the service life of parts. It shows broad application prospects in the preparation of wear-resistant coatings on the surfaces of key parts such as aircraft engines, gas turbines, water turbines, shield cutters, coal mine picks, drilling tools, rotary tillage knives, etc.

[0004] Laser cladding technology has the advantages of low heat input, low base material dilution rate, high forming accuracy, and easy automation. It is one of the commonly used surface functional coating preparation technologies and is widely used. However, the physical and chemical properties of diamond and coating substrates such as steel, stainless steel, and high-temperature alloys are quite different. There are large differences in temperature gradient and stress state during the cladding process. After cladding, stress concentration is easily caused near the diamond, forming cracks or even direct cracking, resulting in poor coating performance and the inability to give full play to the wear resistance of the diamond composite coating, which greatly limits the application of diamond composite wear-resistant coatings. Summary of the invention

[0005] To solve the above problems, one of the objects of the present invention is to provide a method for preparing a laser cladding composite coating, which uses a three-beam laser for cladding, has high production efficiency, and can avoid the formation of stress concentration in the coating, thereby improving the wear resistance and stability of the coating.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a laser cladding composite coating comprises the following steps:

[0008] (1) Pre-treat the surface of the base material to be processed;

[0009] (2) setting the parameters of the laser cladding machine, sequentially setting three laser beams along the cladding direction to laser clad the surface of the pretreated base material, sequentially forming a transition layer, a slow-release layer and a wear-resistant layer on the surface of the base material, and obtaining a laser cladding composite coating;

[0010] The three laser beams in step (2) are respectively a first laser beam, a second laser beam and a third laser beam; the wear-resistant layer cladding process uses the first laser beam for preheating, the second laser beam is synchronously fed into the second nickel-based alloy for cladding, and the third laser beam is used to heat the flux-cored welding wire, so that the flux-cored welding wire is melted and mixed with the second nickel-based alloy to form a wear-resistant layer (diamonds are concentratedly distributed on the upper surface of the wear-resistant layer, further increasing the wear resistance of the coating); the flux core of the flux-cored welding wire includes: diamond.

[0011] Based on the fact that the second nickel-based alloy can not only produce metallurgical bonding with diamond, but also form hard phases such as CrB, Ni3Si, Ni3B with the flux-cored welding wire, which can improve the wear resistance of the coating as a whole, the second nickel-based alloy and the flux-cored welding wire containing diamond are selected as the material of the wear-resistant layer.

[0012] Furthermore, the flux core of the flux cored welding wire is calculated by weight: 60 to 80 parts of diamond, 5 to 15 parts of boron powder, 15 to 25 parts of carbon powder, and the coating is steel skin; the second nickel-based alloy is calculated by weight: 60 to 80 parts of nickel powder, 5 to 11 parts of chromium powder, 5 to 10 parts of silicon powder, and 10 to 20 parts of molybdenum powder; the flux cored welding wire and the second nickel-based alloy are mixed in a ratio of (0.9 to 1.1): 1; the particle size of the diamond is 45 to 100 μm. Since diamond will partially graphitize during the laser cladding process, a particle size that is too small will affect the wear resistance of the diamond under the influence of graphitization, and a particle size that is too large will easily cause uneven wear during the use of the coating, and the diamond is easy to fall off, so the particle size of the diamond of the present invention is 45 to 100 μm.

[0013] Furthermore, the transition layer cladding process uses a first laser beam for preheating, and a second laser beam is simultaneously fed into the first nickel-based alloy for cladding; during the slow-release layer cladding process, pure copper powder is simultaneously fed, and the cladding process only uses the second laser beam.

[0014] The transition layer cladding process of the present invention only uses the first laser beam and the second laser beam. The first laser beam preheats the base material, and the second laser beam clads the transition layer. The preheating can slow down the cooling rate of the subsequent pass to avoid the occurrence of cracks. At the same time, the surface of the base material is roughened and cleaned to improve the coating's wetting performance and coating cleanliness.

[0015] Furthermore, the first nickel-based alloy is composed of nickel powder, chromium powder, molybdenum powder, iron powder, and at least one of the following four components: aluminum powder, titanium powder, manganese powder, and silicon powder; by weight, the nickel powder is 58-62 parts, the chromium powder is 18-23 parts, the molybdenum powder is 7-12 parts, the iron powder is 4-7 parts, the aluminum powder is 0.3-0.5 parts, the titanium powder is 0.3-0.5 parts, the manganese powder is 0.4-0.6 parts, and the silicon powder is 0.4-0.6 parts; the particle size of the pure copper powder is 25-50 μm. In order to avoid the high reflectivity of the pure copper powder to the laser, which makes it difficult to melt, the particle size of the pure copper powder used in the present invention is 25-50 μm.

[0016] The present invention selects the first nickel-based alloy as the cladding transition layer based on the fact that the first nickel-based alloy has good wettability and spreadability, can form a good metallurgical bond with the base material, and has excellent overall toughness of the welded joint; based on the fact that the pure copper powder has a large solid solubility with the transition layer of the first nickel-based alloy, can form a solid solution with the transition layer of the first nickel-based alloy, and the pure copper powder has a good plastic reserve, can buffer stress during the welding process of the diamond coating and during service, and the slow-release layer of the pure copper powder can form a good bond with the wear-resistant layer and can effectively prevent the cracks of the wear-resistant layer from extending to the base material, etc., pure copper powder is selected as the material of the slow-release layer.

[0017] Furthermore, the parameters of the wear-resistant layer cladding are: the first laser power is 500-800W, the second laser power is 800-1200W, the third laser power is 700-900W, the cladding speed is 0.1-0.2m / min, the powder disk speed is 2-3r / min, the carrier gas flow rate is 4-6L / min, and the overlap rate is 40%-50%.

[0018] Furthermore, the parameters of the transition layer cladding are: the first laser power is 500-800W, the second laser power is 800-1200W, the third laser power is 0, the cladding speed is 0.15-0.3m / min, the powder disk speed is 1-2r / min, the carrier gas flow rate is 2-3L / min, and the overlap rate is 30%-40%.

[0019] Furthermore, the parameters of the sustained-release layer cladding are: the first laser power is 0, the second laser power is 900-1200W, the third laser power is 0, the cladding speed is 0.2-0.3m / min, the powder disk speed is 1-2r / min, the carrier gas flow rate is 2-3L / min, and the overlap rate is 30%-40%.

[0020] Furthermore, the first laser beam is a rectangular spot with a size of 10 mm×3 mm; the second laser beam is a circular spot with a diameter of 2 to 3 mm; and the third laser beam is a rectangular spot with a size of 10 mm×3 mm.

[0021] Furthermore, the parent material is any one of low alloy high strength steel, carbon steel, and weathering steel.

[0022] The second object of the present invention is to provide a laser cladding composite coating, which can solve the problem of easy cracking and poor wear resistance of the laser cladding diamond composite wear-resistant coating through the structure of three layers of gradient transition cladding layers.

[0023] A laser cladding composite coating is prepared by the above-mentioned preparation method. The laser cladding composite coating includes a transition layer, a slow-release layer and a wear-resistant layer arranged in sequence from the surface of a base material to the outside. The wear-resistant layer is a diamond composite coating, and diamonds are distributed on the upper surface of the wear-resistant layer.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) In the preparation method provided by the present invention, when preparing the wear-resistant layer, a first laser beam is used for preheating, a second laser beam is used for synchronously feeding a second nickel-based alloy for cladding, and a third laser beam is used to heat the flux-cored welding wire, so that the flux-cored welding wire is melted and mixed with the second nickel-based alloy, so that the diamonds are concentratedly distributed on the upper surface of the wear-resistant layer, thereby increasing the wear resistance of the coating;

[0026] (2) The preparation method of the present invention uses three-beam laser cladding, which has high production efficiency and can also avoid the formation of stress concentration in the coating, thereby improving the wear resistance and use stability of the coating;

[0027] (3) The cladding composite coating of the present invention adopts a three-layer gradient transition cladding layer structure of a transition layer, a slow-release layer and a wear-resistant layer, which can effectively avoid cracks and defects in the diamond laser cladding coating, improve the wear resistance and reliability of the coating, greatly extend the service life of the workpiece, and has significant green benefits and economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the structure of the laser cladding composite coating of the present invention;

[0029] Figure 2 The present invention is a schematic diagram of a device for preparing a laser cladding composite coating using three laser beams.

[0030] Description of reference numerals:

[0031] Among them, 1. base material; 2. transition layer; 3. slow-release layer; 4. wear-resistant layer; 5. diamond; 6. second nickel-based alloy; 8. laser cladding composite coating; 9. first laser beam; 10. second laser beam; 11. third laser beam; 12. coaxial powder feeding laser cladding gun head. DETAILED DESCRIPTION

[0032] The technical scheme of the present invention is further described below in conjunction with specific embodiments. However, it should be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. In the following examples, the raw materials involved are conventional commercially available products unless otherwise specified.

[0033] Among them, the model of the powder feeder is RC-PGF-D double-barrel powder feeder.

[0034] In the following examples, the particle size of the pure copper powder is 25-50 μm, and the particle size of the diamond is 45-100 μm.

[0035] 1. Implementation

[0036] Example 1

[0037] Embodiment 1 provides a method for preparing a laser cladding composite coating, and the specific steps are as follows:

[0038] (1) Pretreatment: sandblast the surface of the low-alloy high-strength steel of the base material to be processed to clean the oil and rust on the surface;

[0039] (2) Setting the laser position: Turn on the laser cladding machine and sequentially set three laser beams along the cladding direction, namely, the first laser beam 9, the second laser beam 10 and the third laser beam 11. The first laser beam 9 is a rectangular spot with a size of 10 mm × 3 mm, the second laser beam 10 is a circular spot with a diameter of 2 mm, and the third laser beam 11 is a rectangular spot with a size of 10 mm × 3 mm.

[0040] (3) Preparation of transition layer 2: setting the power of the first laser beam 9 to 500 W, the power of the second laser beam 10 to 800 W, the power of the third laser beam 11 to 0, the cladding speed to 0.15 m / min, the powder disk speed to 1 r / min, the carrier gas (helium) flow rate to 2 L / min, the overlap rate to 30%, and performing transition layer cladding on the surface of the pretreated low-alloy high-strength steel base material 1 to obtain the transition layer 2. During the cladding process of the transition layer, the first nickel-based alloy (60 parts of nickel powder, 20 parts of chromium powder, 10 parts of molybdenum powder, 5 parts of iron powder, and 0.5 parts of aluminum powder) is simultaneously fed through the coaxial powder feeding laser cladding gun head 12;

[0041] (4) Preparation of sustained-release layer 3: setting the power of the first laser beam 9 to 0, the power of the second laser beam 10 to 900 W, the power of the third laser beam 11 to 0, the cladding speed to 0.2 m / min, the powder disk speed to 1 r / min, the carrier gas (helium) flow rate to 2 L / min, the overlap rate to 30%, and performing sustained-release layer cladding on the surface of the transition layer to obtain a sustained-release layer 3. During the cladding process of the sustained-release layer, pure copper powder is synchronously fed into the laser cladding gun head 12 using a coaxial powder feeding type;

[0042] (5) Preparation of wear-resistant layer 4: The power of the first laser beam 9 is set to 500 W, the power of the second laser beam 10 is set to 800 W, the power of the third laser beam 11 is set to 700 W, the cladding speed is set to 0.1 m / min, the powder disk speed is set to 2 r / min, the carrier gas (helium) flow rate is set to 4 L / min, the overlap rate is set to 40%, the first laser beam 9 is preheated, the second laser beam 10 is simultaneously fed into the second nickel-based alloy 6 (composed of 70 parts of nickel powder, 8 parts of chromium powder, 7 parts of silicon powder, and 15 parts of molybdenum powder) for cladding, and the third laser beam 11 is used to heat the flux-cored welding wire (the flux core is composed of 70 parts of diamond, 12 parts of boron powder, and 18 parts of carbon powder, and the flux coating is steel skin) to melt the flux-cored welding wire and mix it with the second nickel-based alloy in a ratio of 0.9:1, and the wear-resistant layer is clad on the surface of the sustained-release layer to form a diamond 5 located on the upper surface of the wear-resistant layer, thereby obtaining a laser cladding composite coating 8.

[0043] A laser cladding composite coating is prepared by adopting the above preparation method.

[0044] Example 2

[0045] Embodiment 2 provides a method for preparing a laser cladding composite coating, and the specific steps are as follows:

[0046] (1) Pretreatment: sandblast the surface of the carbon steel of the base material to be processed to clean the oil and rust on the surface;

[0047] (2) Setting the laser position: Turn on the laser cladding machine and sequentially set three laser beams along the cladding direction, namely, the first laser beam 9, the second laser beam 10 and the third laser beam 11. The first laser beam 9 is a rectangular spot with a size of 10 mm × 3 mm, the second laser beam 10 is a circular spot with a diameter of 3 mm, and the third laser beam 11 is a rectangular spot with a size of 10 mm × 3 mm.

[0048] (3) Preparation of transition layer 2: setting the power of the first laser beam 9 to 600 W, the power of the second laser beam 10 to 900 W, the power of the third laser beam 11 to 0, the cladding speed to 0.2 m / min, the powder disk speed to 1.5 r / min, the carrier gas (helium) flow rate to 2.5 L / min, the overlap rate to 30%, and performing transition layer cladding on the surface of the pretreated base material 1 carbon steel to obtain the transition layer 2. During the cladding process of the transition layer, the first nickel-based alloy (58 parts of nickel powder, 22 parts of chromium, 12 parts of molybdenum powder, 7 parts of iron powder, 0.3 parts of aluminum powder, and 0.5 parts of titanium powder) was simultaneously fed through the coaxial powder feeding laser cladding gun head 12;

[0049] (4) Preparation of sustained-release layer 3: setting the power of the first laser beam 9 to 0, the power of the second laser beam 10 to 1000 W, the power of the third laser beam 11 to 0, the cladding speed to 0.25 m / min, the powder disk speed to 1.5 r / min, the carrier gas (helium) flow rate to 2.5 L / min, the overlap rate to 30%, and performing sustained-release layer cladding on the surface of the transition layer to obtain a sustained-release layer 3. During the cladding process of the sustained-release layer, pure copper powder is simultaneously fed into the cladding gun head 12 using a coaxial powder feeding laser cladding gun head;

[0050] (5) Preparation of wear-resistant layer 4: The power of the first laser beam 9 is set to 600 W, the power of the second laser beam 10 is set to 900 W, the power of the third laser beam 11 is set to 800 W, the cladding speed is set to 0.15 m / min, the powder disk speed is set to 2.5 r / min, the carrier gas (helium) flow rate is set to 5 L / min, the overlap rate is set to 45%, the first laser beam 9 is preheated, the second laser beam 10 is simultaneously fed into the second nickel-based alloy 6 (60 parts of nickel powder, 11 parts of chromium powder, 10 parts of silicon powder, and 20 parts of molybdenum powder) for cladding, and the third laser beam 11 is used to heat the flux-cored welding wire (core: 60 parts of diamond, 15 parts of boron powder, 25 parts of carbon powder, and the coating is steel skin) to melt the flux-cored welding wire and mix it with the second nickel-based alloy in a ratio of 1:1, and the wear-resistant layer is clad on the surface of the sustained-release layer to form a diamond 5 located on the upper surface of the wear-resistant layer to obtain a laser cladding composite coating 8.

[0051] A laser cladding composite coating is prepared by adopting the above preparation method.

[0052] Example 3

[0053] Embodiment 3 provides a method for preparing a laser cladding composite coating, and the specific steps are as follows:

[0054] (1) Pretreatment: sandblast the surface of the weathering steel to be processed to clean the oil and rust on the surface;

[0055] (2) Setting the laser position: Turn on the laser cladding machine and sequentially set three laser beams along the cladding direction, namely, the first laser beam 9, the second laser beam 10 and the third laser beam 11. The first laser beam 9 is a rectangular spot with a size of 10 mm × 3 mm, the second laser beam 10 is a circular spot with a diameter of 2.5 mm, and the third laser beam 11 is a rectangular spot with a size of 10 mm × 3 mm.

[0056] (3) Preparation of transition layer 2: setting the power of the first laser beam 9 to 600 W, the power of the second laser beam 10 to 1000 W, the power of the third laser beam 11 to 0, the cladding speed to 0.2 m / min, the powder disk speed to 2 r / min, the carrier gas (helium) flow rate to 3 L / min, the overlap rate to 35%, and performing transition layer cladding on the surface of the pretreated base material 1 weathering steel to obtain the transition layer 2. During the cladding process of the transition layer, the first nickel-based alloy (62 parts of nickel powder, 18 parts of chromium powder, 7 parts of molybdenum powder, 4 parts of iron powder, 0.3 parts of aluminum powder, 0.5 parts of titanium powder, and 0.6 parts of manganese powder) is simultaneously fed through the coaxial powder feeding laser cladding gun head 12;

[0057] (4) Preparation of sustained-release layer 3: setting the power of the first laser beam 9 to 0, the power of the second laser beam 10 to 1200 W, the power of the third laser beam 11 to 0, the cladding speed to 0.3 m / min, the powder disk speed to 2 r / min, the carrier gas (helium) flow rate to 3 L / min, the overlap rate to 35%, and performing sustained-release layer cladding on the surface of the transition layer to obtain a sustained-release layer 3. During the cladding process of the sustained-release layer, pure copper powder is synchronously fed into the laser cladding gun head 12 using a coaxial powder feeding type;

[0058] (5) Preparation of wear-resistant layer 4: The power of the first laser beam 9 is set to 700 W, the power of the second laser beam 10 is set to 1100 W, the power of the third laser beam 11 is set to 900 W, the cladding speed is set to 0.15 m / min, the powder disk speed is set to 2.5 r / min, the carrier gas (helium) flow rate is set to 5 L / min, the overlap rate is set to 45%, the first laser beam 9 is preheated, the second laser beam 10 is simultaneously fed into the second nickel-based alloy 6 (80 parts of nickel powder, 5 parts of chromium powder, 5 parts of silicon powder, and 10 parts of molybdenum powder) for cladding, and the third laser beam 11 is used to heat the flux-cored welding wire (core: 80 parts of diamond, 5 parts of boron powder, 15 parts of carbon powder, and the coating is steel skin) to melt the flux-cored welding wire and mix it with the second nickel-based alloy in a ratio of 1.1:1, and the wear-resistant layer is clad on the surface of the sustained-release layer to form a diamond 5 located on the upper surface of the wear-resistant layer to obtain a laser cladding composite coating 8.

[0059] A laser cladding composite coating is prepared by adopting the above preparation method.

[0060] Example 4

[0061] Embodiment 4 provides a method for preparing a laser cladding composite coating, and the specific steps are as follows:

[0062] (1) Pretreatment: sandblast the surface of the low-alloy high-strength steel of the base material to be processed to clean the oil and rust on the surface;

[0063] (2) Setting the laser position: Turn on the laser cladding machine and sequentially set three laser beams along the cladding direction, namely, the first laser beam 9, the second laser beam 10 and the third laser beam 11. The first laser beam 9 is a rectangular spot with a size of 10 mm × 3 mm, the second laser beam 10 is a circular spot with a diameter of 2 mm, and the third laser beam 11 is a rectangular spot with a size of 10 mm × 3 mm.

[0064] (3) Preparation of transition layer 2: setting the power of the first laser beam to 800 W, the power of the second laser beam to 1200 W, the power of the third laser beam to 0, the cladding speed to 0.3 m / min, the powder disk speed to 2 r / min, the carrier gas (helium) flow rate to 3 L / min, the overlap rate to 40%, and performing transition layer cladding on the surface of the pretreated low-alloy high-strength steel base material 1 to obtain transition layer 2. During the cladding process of the transition layer, a first nickel-based alloy (60 parts of nickel powder, 20 parts of chromium powder, 10 parts of molybdenum powder, 5 parts of iron powder, 0.3 parts of aluminum powder, 0.5 parts of titanium powder, 0.6 parts of manganese powder, and 0.6 parts of silicon powder) is simultaneously fed into the coaxial powder feeding laser cladding gun head 12;

[0065] (4) Preparation of sustained-release layer 3: setting the power of the first laser beam 9 to 0, the power of the second laser beam 10 to 1200 W, the power of the third laser beam 11 to 0, the cladding speed to 0.3 m / min, the powder disk speed to 2 r / min, the carrier gas (helium) flow rate to 3 L / min, the overlap rate to 40%, and performing sustained-release layer cladding on the surface of the transition layer to obtain a sustained-release layer 3. During the cladding process of the sustained-release layer, pure copper powder is synchronously fed into the laser cladding gun head 12 using a coaxial powder feeding type;

[0066] (5) Preparation of wear-resistant layer 4: The power of the first laser beam 9 is set to 800 W, the power of the second laser beam 10 is set to 1200 W, the power of the third laser beam 11 is set to 700 W, the cladding speed is set to 0.2 m / min, the powder disk speed is set to 3 r / min, the carrier gas (helium) flow rate is set to 6 L / min, the overlap rate is set to 50%, the first laser beam 9 is preheated, the second laser beam 10 is simultaneously fed into the second nickel-based alloy 6 (70 parts of nickel powder, 8 parts of chromium powder, 7 parts of silicon powder, and 15 parts of molybdenum powder) for cladding, and the third laser beam 11 is used to heat the flux-cored welding wire (core: 70 parts of diamond, 12 parts of boron powder, 18 parts of carbon powder, and the coating is steel skin) to melt the flux-cored welding wire and mix it with the second nickel-based alloy in a ratio of 1:1, and the wear-resistant layer is clad on the surface of the sustained-release layer to form a diamond 5 located on the upper surface of the wear-resistant layer (, and a laser cladding composite coating 8 is obtained.

[0067] A laser cladding composite coating is prepared by adopting the above preparation method.

[0068] 2. Comparison

[0069] Comparative Example 1

[0070] Comparative Example 1 provides a coating and a preparation method thereof, and the specific process is as follows:

[0071] Steps (1) to (4) are the same as in Example 1;

[0072] (5) Preparation of wear-resistant layer: The power of the first laser beam was set to 500 W, the power of the second laser beam was set to 800 W, the power of the third laser beam was set to 500 W, the cladding speed was set to 0.1 m / min, the powder disk speed was set to 2 r / min, the carrier gas (helium) flow rate was set to 4 L / min, the overlap rate was set to 40%, and during the cladding process of the wear-resistant layer, a mixed powder of diamond and a second nickel-based alloy (the balance) accounting for 70% by volume was simultaneously fed to obtain a wear-resistant layer, and the diamond was dispersed throughout the wear-resistant layer.

[0073] Comparative Example 2

[0074] Comparative Example 2 provides a coating and a preparation method thereof, and the specific process is as follows:

[0075] Steps (1) to (2) are the same as in Example 1;

[0076] (3) Preparation of wear-resistant layer: The power of the first laser beam was set to 500 W, the power of the second laser beam was set to 800 W, the power of the third laser beam was set to 500 W, the cladding speed was set to 0.1 m / min, the powder disk speed was set to 2 r / min, the carrier gas (helium) flow rate was set to 4 L / min, the overlap rate was set to 40%, the first laser beam was used for preheating, the second laser beam was used for synchronous cladding of the second nickel-based alloy, and the third laser beam was used for heating the flux-cored welding wire (flux core: 70 parts of diamond, 12 parts of boron powder, 18 parts of carbon powder, and the coating was steel coating) to melt the flux-cored welding wire and mix it with the second nickel-based alloy (70 parts of nickel powder, 8 parts of chromium powder, 7 parts of silicon powder, and 15 parts of molybdenum powder) in a ratio of 0.9:1, and the wear-resistant layer was clad on the surface of the pretreated low-alloy high-strength steel.

[0077] Comparative Example 3

[0078] Comparative Example 3 provides a coating and a preparation method thereof, and the specific process is as follows:

[0079] Steps (1) to (2) are the same as in Example 1;

[0080] (3) Preparation of transition layer: setting the power of the first laser beam to 500 W, the power of the second laser beam to 800 W, the power of the third laser beam to 0, the cladding speed to 0.15 m / min, the powder disk speed to 1 r / min, the carrier gas (helium) flow rate to 2 L / min, the overlap rate to 30%, and performing transition layer cladding on the surface of the pretreated low-alloy high-strength steel to obtain a transition layer. During the cladding process of the transition layer, Ni-Cr-Fe alloy (59% nickel, 30% chromium, 9% iron, 0.2% carbon, 0.22% aluminum, 0.26% Ti, 0.23% Mn, 0.07% silicon, 0.02% copper, and the remainder being impurities of copper and phosphorus) is simultaneously introduced; steps (4) to (5) are the same as in Example 1.

[0081] Comparative Example 4

[0082] Comparative Example 4 provides a coating and a preparation method thereof, which differs from Example 1 in that step (3) of preparing the transition layer is omitted, and the rest is the same as Example 1.

[0083] Comparative Example 5

[0084] Comparative Example 5 provides a coating and a preparation method thereof, which is different from Example 1 in that step (4) of preparing the sustained-release layer is omitted, and the rest is the same as Example 1.

[0085] 3. Test Examples

[0086] Test Example 1

[0087] Test Example 1 The surface quality and wear performance of the coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were investigated. The results are shown in Table 1.

[0088] Table 1

[0089]

[0090] As shown in Table 1, compared with Comparative Example 1 (sending diamond and the second nickel-based alloy powder simultaneously to obtain a wear-resistant layer, wherein diamond is dispersed throughout the wear-resistant layer, and the content of diamond in the upper part of the wear-resistant layer is relatively low), Comparative Example 2 (setting the wear-resistant layer directly on the surface of the parent material), Comparative Example 3 (adjusting the material of the transition layer), Comparative Example 4 (omitting the transition layer), and Comparative Example 5 (omitting the slow-release layer), the laser cladding composite coatings prepared in Examples 1 to 3 have no cracks after cladding, and exhibit good wear resistance in actual testing. This shows that the preparation method provided by the present invention can improve the wear resistance and performance of the coating.

[0091] In summary, when preparing the wear-resistant layer, the preparation method provided by the present invention uses a first laser beam for preheating, a second laser beam is synchronously fed into the second nickel-based alloy for cladding, and a third laser beam is used to heat the flux-cored wire, so that the flux-cored wire is melted and mixed with the second nickel-based alloy, so that the diamonds are concentrated on the upper surface of the wear-resistant layer, further increasing the wear resistance of the coating. The preparation method of the present invention also uses three-beam laser cladding, which has high production efficiency, and can avoid the formation of stress concentration in the coating, improve the wear resistance and use stability of the coating. The coating of the present invention adopts a three-layer gradient transition cladding layer structure of a transition layer, a slow-release layer and a wear-resistant layer, which can effectively alleviate the stress concentration caused by the large difference in the physical and chemical properties between the base material and the diamond, avoid the formation of cracks in the coating, improve the wear resistance and use performance of the coating, and ensure the safe and reliable service of parts.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. On the basis of the present invention, some modifications or replacements may be made thereto, but these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of protection claimed by the present invention.

Claims

1. A method for preparing a laser cladding composite coating, characterized in that: The following steps are involved: (1) Pre-treat the surface of the base material to be processed; (2) Setting the parameters of the laser cladding machine, sequentially setting three laser beams along the cladding direction to laser clad the surface of the pretreated base material, sequentially forming a transition layer, a slow-release layer and a wear-resistant layer on the surface of the base material, and obtaining a laser cladding composite coating; The three laser beams in step (2) are respectively a first laser beam, a second laser beam and a third laser beam; the first laser beam is used for preheating during the wear-resistant layer cladding process, the second laser beam is used for synchronously feeding the second nickel-based alloy for cladding, and the third laser beam is used for heating the flux-cored welding wire, so that the flux-cored welding wire is melted and mixed with the second nickel-based alloy to form a wear-resistant layer; diamond is added to the flux core of the flux-cored welding wire; the first laser beam is used for preheating during the transition layer cladding process, and the second laser beam is used for synchronously feeding the first nickel-based alloy for cladding; pure copper powder is simultaneously fed into the sustained-release layer cladding process, and only the second laser beam is used in the cladding process; The composition of the flux core of the flux cored welding wire is calculated by weight: 60-80 parts of diamond, 5-15 parts of boron powder, and 15-25 parts of carbon powder; the coating of the flux cored welding wire is steel coating; the composition of the second nickel-based alloy is calculated by weight: 60-80 parts of nickel powder, 5-11 parts of chromium powder, 5-10 parts of silicon powder, and 10-20 parts of molybdenum powder; the flux cored welding wire and the second nickel-based alloy are mixed in a ratio of (0.9-1.1):1; The first nickel-based alloy composition comprises: nickel powder, chromium powder, molybdenum powder, iron powder, and at least one of the following four components: aluminum powder, titanium powder, manganese powder, and silicon powder; in parts by weight, the nickel powder comprises 58 to 62 parts, the chromium powder comprises 18 to 23 parts, the molybdenum powder comprises 7 to 12 parts, the iron powder comprises 4 to 7 parts, the aluminum powder comprises 0.3 to 0.5 parts, the titanium powder comprises 0.3 to 0.5 parts, the manganese powder comprises 0.4 to 0.6 parts, and the silicon powder comprises 0.4 to 0.6 parts.

2. The method for preparing a laser cladding composite coating according to claim 1, characterized in that: The particle size of the diamond is 45-100 μm.

3. The method for preparing a laser cladding composite coating according to claim 1, characterized in that: The particle size of the pure copper powder is 25-50 μm.

4. The method for preparing a laser cladding composite coating according to claim 1, characterized in that: The parameters of the wear-resistant layer cladding are: the first laser power is 500~800W, the second laser power is 800~1200W, the third laser power is 700~900W, the cladding speed is 0.1~0.2m / min, the powder disk speed is 2~3r / min, the carrier gas flow rate is 4~6L / min, and the overlap rate is 40%~50%.

5. The method for preparing a laser cladding composite coating according to claim 1, characterized in that: The parameters of the transition layer cladding are: the first laser power is 500~800W, the second laser power is 800~1200W, the third laser power is 0, the cladding speed is 0.15~0.3m / min, the powder disk speed is 1~2r / min, the carrier gas flow rate is 2~3L / min, and the overlap rate is 30%~40%.

6. The method for preparing a laser cladding composite coating according to claim 1, characterized in that: The parameters of the sustained-release layer cladding are: the first laser power is 0, the second laser power is 900-1200W, the third laser power is 0, the cladding speed is 0.2-0.3m / min, the powder disk speed is 1-2r / min, the carrier gas flow rate is 2-3L / min, and the overlap rate is 30%-40%.

7. The method for preparing a laser cladding composite coating according to claim 1, characterized in that: The first laser beam is a rectangular spot with a size of 10 mm×3 mm; the second laser beam is a circular spot with a diameter of 2-3 mm; and the third laser beam is a rectangular spot with a size of 10 mm×3 mm.

8. The method for preparing a laser cladding composite coating according to claim 1, characterized in that: The parent material is any one of low alloy high strength steel, carbon steel and weathering steel.

9. A laser cladding composite coating, characterized in that: The laser cladding composite coating is prepared by the preparation method according to any one of claims 1 to 8, wherein the laser cladding composite coating comprises a transition layer, a sustained-release layer and a wear-resistant layer arranged in sequence from the surface of the base material to the outside, and the wear-resistant layer is a diamond composite coating, and diamonds are distributed on the upper surface of the wear-resistant layer.

Citation Information

Patent Citations

  • Method for performing laser cladding by using multiple lasers

    CN103774137A

  • Nickel-based composite material based on diamonds of different qualities and preparation method of nickel-based composite material

    CN115948679A